Somatic embryogenesis from leaf transverse thin cell layer derived-callus of Vietnamese ginseng (Panax vietnamensis Ha et Grushv.) - Hien, Vu Thi; Huy, Nguyen Phuc; Vinh, Bui Van The; Chien, Hoang Xuan; Tung, Hoang Thanh; Nam, Nguyen Ba; Luan, Vu Quoc; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2016)
No report on plant regeneration via somatic embryogenesis of P. vietnamensis has been previously published. In the present study, somatic embryogenesis via callus formation from cultures of leaf transverse thin cell layers (tTCLs) of Vietnamese ginseng (Panax vietnamensis Ha et Grushv.) was investigated. α-naphthaleneacetic acid (NAA), 2,4-dichlorophenoxyacetic acid (2,4-D), 6-benzylaminopurine (BA) and thidiazuron (TDZ) were added separately and in combination into the culture media. Explant necrosis or low callogenesis rates were observed when 1-mm wide leaf tTCLs were cultured on media with TDZ, BA, 2,4-D or NAA. On the other hand, calli were successfully induced from the tTCL explants cultured on medium supplemented with either 2,4-D and BA or 2,4-D and TDZ. Callogenesis was observed under both light and dark conditions. The highest callogenesis rate (100%) was obtained on Murashige and Skoog (MS) basal medium supplemented with 1.0 mg l-1 2,4-D in combination with 0.1 mg l-1 TDZ in darkness after eight weeks of culture. White calli were cut into small pieces (1.0 x 1.0 cm dimension) and placed on MS media containing 1.0 mg l-1 2,4-D, 0.5 mg l-1 NAA and TDZ at various concentrations (0.01; 0.1; 0.2; and 0.5 mg l-1), and the best callus proliferation was recorded on medium containing 1.0 mg l-1 2,4-D and 0.2 mg l-1 TDZ. Somatic embryogenesis, with a success rate of 53.3% and 35 embryos per explant, was achieved when calli were subcultured onto MS medium supplemented with 1.0 mg l-1 2,4-D, 0.5 mg l-1 NAA and 0.2 mg l-1 TDZ